Polarisation News Consumption and Beliefs in Misinformation and Conspiracy Theories: Early Signs of the Fragmentation of the Public Sphere in Iceland - Ólafsson, Jón Gunnar; Jóhannsdóttir, Valgerður (Javnost-The Public, 2024)
A common explanation linked to increased polarisation has focused on changes in citizens’ information diets, with like-minded people apparently becoming increasingly isolated in online echo chambers. This article investigates whether news audience polarisation has increased in Iceland in recent years and if there is polarisation in Icelandic society concerning beliefs in misinformation and conspiracy theories. Iceland is an interesting case study since it is very small and still quite homogenous, but experiencing rapid societal changes and a media landscape in turmoil. We utilise data from representative surveys conducted in 2017 and 2022. Findings show that news consumption patterns in Iceland have shifted towards online platforms, with a significant increase in online news consumption across all age groups, and a decline in the use of traditional legacy outlets. News audience polarisation appears, however, to remain relatively low in Iceland, with most news brands reaching a mixed and centrist audience. We find that gender, education, and political ideology are related to beliefs concerning misinformation and conspiracy theories focused on climate change and refugees. Moreover, our results suggest that trust in the mainstream media, as well as news consumption from partisan outlets, are related to beliefs in misinformation and conspiracy theories.